Konfigurasi Politik Hukum Terhadap Penghapusan Proses Peradilan dalam Undang-Undang No 16 Tahun 2017 Tentang Organisasi Masyarakat - Robby Aulia Hidayat (Journal Law and Government, 2025)
Law Number 16 of 2017 on Community Organizations was enacted as the government’s response to organizations deemed contrary to Pancasila and the 1945 Constitution. The most significant change introduced by this law is the elimination of judicial mechanisms in the dissolution of organizations, which had previously been required under Law Number 17 of 2013. This study applies Mahfud MD’s theory of political configuration of law to analyze the political dynamics behind the regulation. The findings show that removing the due process of law strengthens the dominance of the executive branch and undermines both the rule of law and the constitutional right to freedom of association. Therefore, Law Number 16 of 2017 reflects a conservative legal product shaped by an authoritarian political configuration.